2020
DOI: 10.21203/rs.3.rs-16087/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compositional and functional characterisation of biomass-degrading microbial communities in guts of plant fibre- and soil-feeding higher termites

Abstract: Background: Termites are among the most successful insect lineages on the globe and are responsible for providing numerous ecosystem services. They mainly feed on wood and other plant material at different stages of humification. Lignocellulose is often a principal component of such plant diet and termites largely rely on their symbiotic microbiota and associated enzymes to decompose their food efficiently. While lower termites and their gut flagellates were given larger scientific attention in the past, the g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 44 publications
5
14
0
Order By: Relevance
“…Contigs including genes with discordant taxonomic annotations potentially indicate horizontal gene transfers, as is common among bacteria (Ochman et al ., 2000), and were removed. We found that Bacteroidota were a significant source of GH2, GH9, GH10, GH20, GH28, GH29, GH30, GH31, and GH130 in FC and LT, while, as previously described (Marynowska et al ., 2020), they rarely encoded these GHs in non-Macrotermitinae Termitidae (WF and SF) (Figure 4, Table S8). In contrast, Fibrobacteres, which were very rare in LT, were a significant source of GH2, GH3, GH8, GH9, GH10, GH11, GH18, GH26, GH30, GH43, GH94, and GH130 in WF.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Contigs including genes with discordant taxonomic annotations potentially indicate horizontal gene transfers, as is common among bacteria (Ochman et al ., 2000), and were removed. We found that Bacteroidota were a significant source of GH2, GH9, GH10, GH20, GH28, GH29, GH30, GH31, and GH130 in FC and LT, while, as previously described (Marynowska et al ., 2020), they rarely encoded these GHs in non-Macrotermitinae Termitidae (WF and SF) (Figure 4, Table S8). In contrast, Fibrobacteres, which were very rare in LT, were a significant source of GH2, GH3, GH8, GH9, GH10, GH11, GH18, GH26, GH30, GH43, GH94, and GH130 in WF.…”
Section: Resultssupporting
confidence: 88%
“…Therefore, the primary contributors of GHs are distinct between lower and higher termites. These results are consistent with previous reports indicating a possible involvement of the ectosymbiotic Bacteroidota of some oxymonadid flagellates in cellulose and hemicellulose hydrolysis (Yuki et al, 2015;Treitli et al, 2019) in lower termites, while Fibrobacteres, Spirochaeota, and/or Firmicutes are major agents in cellulose and hemicellulose degradation in higher termites (Warneke et al, 2007;He et al, 2013;Tokuda et al, 2018;Calusinska et al, 2020;Marynowska et al, 2020). Our comprehensive analyses strongly indicate that the loss of cellulolytic flagellates in the ancestor of higher termites was accompanied by a major reworking of the cellulolytic bacterial communities, from Bacteroidota in LT to Fibrobacterota and Spirochaeota in WF and to Firmicutes in SF.…”
Section: The Carbohydrate-active Enzymes Of Termite Gut Prokaryotessupporting
confidence: 93%
See 3 more Smart Citations